(untitled) (National Administration Journal, 2023)
Purpose. The literature has long recognized the importance of the conscientious entrepreneurial personality. This study explores how seven of its facets/sub-dimensions (Achievement-Striving, Efficiency, Responsibility, Industriousness, Self-Control, Conventionality, and Persistence) relate to three performance outcomes (Ventures Started, Years at Current Venture, and Annual Sales.) Design/methodology/approach. 166 active entrepreneurs were surveyed via an entrepreneurship center at a Western US university. Data was then modeled via Ordinary Least Squares to obtain regression estimates for the dependent variables. Findings. Counter to expectations, results indicate that facet measures relate very differently in terms of magnitude, direction, and significance to the performance outcomes. These more nuanced relations are lost when using broad/aggregate dimensional measures. Research implications. Broad personality measures, as conventionally used, are suboptimal for entrepreneurial research as they potentially yield misleading results. Studies should instead apply the more-specific facet measures, which offer more accurate personality assessments. Practical implications. Practitioners should also use the more-specific facet measures. Doing so will be of value across a variety of public, private, and educational settings. Originality/Value. For decades, entrepreneurship has addressed the effects of broad/aggregate personality dimensions. This article is the first to approach the entrepreneurial personality from a more-specific facet level, an approach offering substantial research opportunities.